THERMAL CAPACITY OF ENRICHED FUEL BRIQUETS PRODUCED FROM THE FINE OF EKIBASTUS COAL - Abdrakhmanov, Ye.S.; Bogomolov, A.V.; Bykov, P.O.; Kuandikov, A.B. (International Journal of Engineering Technologies and Management Research, 2017)
The object of research or development: The object of the research work was coal fines and processes of enrichment of Ekibastuz coal to produce fuel briquettes with increased calorific value and less ash content. Objective: Research, scientific substantiation of technology for obtaining high-calorific coal briquettes from fines of Ekibastuz coal using various binders and the possibility of further coking, designing and manufacturing equipment for the implementation of technology. Method or methodology of the work: The standard methods of theoretical and experimental research widely used in metallurgy, machine building, computer systems, etc. were used in the work. The results of the work and their novelty: The characteristics of briquettes on bio-binding and on petroleum pitch with enrichers in the form of rubber-technical soot and anode dust of electrolysers for aluminum production have been established. It is revealed that the calorific value of briquettes is higher than that of Ekibastuz coal(Pavlodar region) by 20-40%, and the heating value is the highest for briquettes with an enrichment agent in the form of anode dust and a binder in the form of petroleum pitch (-NH combustion = 6840.8 kcal / kg). The structures of the soot separator, sorting and sifting equipment, mixing laboratory equipment, the mouthend briquetting press, the briquetting press and the screw mixer with the heater have been designed. Based on the results of the research, the project manager and co-authors published 15 scientific publications, patents and theses of international conferences. Application area: Briquettes for bio-binding can be used as fuel for combustion in centralized village boiler houses, private houses and farms. Briquettes on petroleum pitch with an enrichment agent in the form of anodic dust of aluminum electrolysis can be used as industrial briquettes for further use in metallurgy. Forecasting assumptions about the development of the object of research: Further studies are required to assess the feasibility of using industrial briquettes for coking and use in metallurgy, the manufacture of laboratory and research equipment to further commercialize the project.